COVID-19 and the cardiovascular system - Lysenko, O. K. (Запорізький державний медичний університет, 2022)
The purpose of the study: to analyze current scientific literature and understanding the damage caused by SARS- CoV-2 to the cardiovascular system and the underlying mechanisms is of the greatest importance.
Keywords: тези доповідей